Designing and implementing a resiliency program for family medicine residents. (July 2015) - Brennan, Julie; McGrady, Angele
Family medicine residents are at risk for burnout due to extended work hours, lack of control over their work schedule, and challenging work situations and environments. Building resiliency can prevent burnout and may improve a resident's quality of life and health behavior. This report describes a program designed to build resiliency, the ability to bounce back from stress, in family medicine residents in a medium sized U.S. residency training program. Interactive sessions emphasized building self-awareness, coping skills, strengths and meaning in work, time management, self-care, and connections in and outside of medicine to support resident well-being. System changes which fostered wellness were also implemented. These changes included increasing the availability of fresh fruits in the conference and call room, purchasing an elliptical exercise machine for the on call room, and offering a few minutes of mindfulness meditation daily to the inpatient residents. Results to date show excellent acceptance of the program by trainees, increased consumption of nutritious foods, more personal exercise, and self-reported decreased overreactions to stress. Resiliency programs can effectively serve to meet accreditation requirements while fostering residents' abilities to balance personal and professional demands.